Effect of Preoperative Internal Biliary Drainage on Postoperative Outcome Following Pancreaticoduodenectomy for Periampullary Carcinoma (KYAMC Journal, 2020)
Background: Preoperative biliary drainage before pancreaticoduodenectomy is a controversial issue. Proponents are in favor of preoperative biliary drainage by ERCP with stent to reduce surgical jaundice with an anticipation of better surgical outcome.Objective: Compare the outcome with or without pre-operative biliary drainage before pancreaticoduodenectomy.Materials and Methods: This observational comparative study was conducted in department of Surgery and Hepatobiliary and pancreatic surgery of BSMMU. Twenty three patients presented with obstructive jaundice due to periampulary carcinoma who subsequently underwent pancreaticoduodenectomy were selected by purposive sampling and finalized by eligibility criteria.Results: Patients with preoperative biliary drainage (PBD) group required a longer operative time (mean 4.12 hours versus 3.83 hours) and had more intra-operative blood loss (mean 662 mL versus 495 mL) compared with non PBD group (P=0.009 and 0.010). No differences were found with respect to operative mortality (4.3%) and incidence of pancreatic leakage (P=0.281). PBD was significantly associated with positive bile culture (P=0.019) and high incidence of wound infection (p=0.029).Conclusion: Preoperative biliary drainage did not increase major postoperative morbidity and mortality but associated with increased operative time, intraoperative blood loss, and incidence of wound infection. Preoperative biliary drainage should be used selectively in patients undergoing pancreaticoduodenectomy.KYAMC Journal Vol. 10, No.-4, January 2020, Page 196-201